Effect of extracorporeal shock wave therapy on scar pain in burn patients: A prospective, randomized, single-blind, placebo-controlled study. Issue 32 (August 2016) - Cho, Yoon Soo; Joo, So Young; Cui, Huisong; Cho, Sung-Rae; Yim, Haejun; Seo, Cheong Hoon
Abstract: Background: Extracorporeal shock wave therapy (ESWT) has been used to reduce pain in patients with various musculoskeletal diseases and wounds. We investigated the effect of ESWT on scar pain after complete wound epithelialization in burn patients. Methods: A prospective, single-blind, placebo-controlled study was conducted from February 2014 to 2015. Forty patients with burn scar pain despite standard therapy (medication, physical therapy, and burn rehabilitation massage therapy) were randomized into ESWT or control (sham ESWT) groups. ESWT was administered at 100 impulses/cm 2 (0.05–0.15 mJ/mm 2 ) once per week for 3 weeks. The treatment effects were assessed using the numerical rating scale (NRS), pain threshold, Nirschl pain phase system, and Roles and Maudsley scores. Results: The characteristics of patients between the 2 study groups were balanced ( P >0.05) for age, sex, and total burn surface area (%). In both groups, the NRS, pain threshold (Ib/cm 2 ), and Nirschl pain phase system values significantly improved ( P <0.05) after 3 sessions of ESWT or sham therapy, and there were significant differences between the 2 groups in terms of these 3 variables ( P <0.001, P <0.001, P = 0.013, respectively). The Roles and Maudsley scores significantly improved; among 20 patients, 17 reported a score of poor (85%) and 3 reported fair (15%) before ESWT, whereas 3 reported poor (15%), 8 reported fair (40%), 5 reported good (25%), and 4 reported excellent (20%) after ESWT ( P = 0.004). The scores did not improve in the control group ( P = 0.128). Conclusion: ESWT significantly reduced scar pain in burn patients after wound recovery.